Moringa Oleifera and Undernutrition: A Narrative Review - Oksidriyani, Safrina (Sean Institute, 2023)
Malnutrition is nutrient deficits or excesses, an imbalance of critical nutrients, or inadequate nutrient utilization. Undernutrition presents itself in four ways: wasting, stunting, underweight, and lacking micronutrients. Meanwhile, overweight and obesity are two forms of overnutrition. In 2020, the World Health Organization projected 149 million stunted children under five, 45 million wasted children, and 38.9 million overweight or obese children. We conducted a comprehensive literature search across databases such as Google Scholar, PubMed, and ScienceDirect. We searched for articles using MeSH-compliant keywords including “Moringa oleifera”, “malnutrition”, “undernutrition”, “stunting”, “wasting”, “growth disorders”, “overnutrition”, “obesity”, and “overweight”,This review included studies published between 1 January 2020 - 31 May 2023 that were human or animal research studies, written in English and were full-length articles. Studies that were (i) not relevant to the main focus of the review; (ii) Ph.D. dissertations, conference proceedings, unpublished studies; (iii) abstracts, case studies, in vitro studies, non-experimental studies, protocols and reviews; and (iv) duplicate were excluded. The key findings of each research project were summarized based on the year, the study group, the technique utilized, the interventions used, the variables considered, the primary outcomes, and the concluding remarks for data interpretation. Moringa oleifera is readily available in Indonesia as a local food ingredient. Studies have demonstrated the beneficial effects of Moringa oleifera on malnutrition, encompassing both undernutrition and overnutrition, through various mechanisms, including enhanced antioxidant capacity and modulation of appetite-regulating hormones.